Generative Electronic Poetic Texts: Specifics of Verbal Component and Peculiarities of Code Structure - S. A. Kuchina (Научный диалог)
The issues related to typification and analysis of electronic program algorithms and online services for electronic poetic texts generation are covered. Special attention is paid to the description of the algorithmic principles of generating poetic texts, based on strophic organization, poetic size, algorithmic syntax, and matrix of phrases. The novelty of the research is seen in the attempt to understand the program algorithms to generate a literary text not only as a method of text creation, but also as a substantive artistic expression, where the code is regarded as a meaning that needs no verbal accompaniment. The research urgency is caused by the attempt to understand and analyse the generative poetic texts of different types (algorithmic, code, Twitter-bots). The article gives an overview of modern online generators and generative poetic texts, represented by the works “POEM.EXE” by L. Kuki, “Frequency” by S. Rettberg, “Code Movie 1” by J. Baigelman and H. Stein. Classification of online generators of poetic texts is given, divided the texts into services for generation of electronic poetic texts on the basis of the lexical material introduced by the user or the author, and the services based on the matrix of phrases.